Kepastian Hukum Aset Kripto sebagai Instrumen Investasi dalam Persfektif hukum islam dan Hukum Positif - Siregar, Emiel Salim; Manurung, Widya; Gunawan, Rudi; Dzulkhairil, Muhammad; Siagian, Ramadhan; Ardiansyah, Muhammad; Lubis, Rusdi; Sitorus, Andreansyah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Cryptocurrency is a virtual currency that has no physical or concrete form and exists in cyberspace. One of several types of crypto money is Crypto Asset. The use of Crypto Assets as a means of payment in online buying and selling transactions has recently become increasingly widespread, even though the government has banned this practice. At the beginning of 2019, the Indonesian government has issued regulations regarding the legalization of Crypto Assets (crypto assets) in Commodity Futures Trading. The dual function of Crypto Asset as a commodity and online transaction exchange tool raises pros and cons among scholars and economists. This study aims to obtain answers regarding cryptocurrencies as a commodity in Indonesia and what are the opportunities for Crypto Assets as subjects in Islamic commodities on the Commodity Exchange. The theory applied is the theory of legal and vanity business transactions in Islam. This research is a literature study and is qualitative in nature. The data analysis technique used is analytical descriptive with a normative juridical Islamic law approach. From this research, the results show that cryptocurrencies can be traded on Islamic commodity exchanges on condition that the state protects this trade under a legal umbrella and issues cryptocurrencies where the price is determined by gold or the country's currency. Crypto Assets cannot be used as commodities in Sharia Derivative Contracts in Indonesia, because Crypto Assets still contain speculation, maysir and are prone to be used for illegal activities. Crypto assets are legally h}aram lighairihi or illegal due to external factors, so they should be avoided. Keywords: Legal Certainty, Crypto Assets, Investment in Islamic Law and Positive Law